2006
DOI: 10.1002/cbm.619
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient risk management with mentally ill offenders: results of a survey on clinical decision‐making about easing restrictions

Abstract: These findings offer some clarification of the concept of clinical judgment as applied to assessment of readiness for discharge of offender patients from specialist forensic psychiatric hospitals. Research into risk assessment and management might be improved by taking account of explicit clinical concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
(17 reference statements)
0
13
0
1
Order By: Relevance
“…Research in Europe, North America and Australia has addressed the practical problems of managing perceived risks in this sector (e.g. Halleck & Petrilla, 1988;Nijman, Merckelbach, Allertz, & a Campo, 1997;Bowles et al, 2002;Quirk, Lelliott, & Seale, 2004;Meehan et al, 2006;Stubner et al, 2006;Cardell, 2009;Fluttert, van Meijel, van Leeuwen, Bjørkly, Nijman, & Grypdonck 2011;Manna, 2010). Such concerns have led to 'the re-articulation of mental health work in the language of risk' (Quirk et al, 2004(Quirk et al, , p. 2574 and the emergence of a new emphasis on confinement within secure buildings, which is of special interest in this paper.…”
Section: Contextualising Our Research In the Interdisciplinary Literamentioning
confidence: 99%
“…Research in Europe, North America and Australia has addressed the practical problems of managing perceived risks in this sector (e.g. Halleck & Petrilla, 1988;Nijman, Merckelbach, Allertz, & a Campo, 1997;Bowles et al, 2002;Quirk, Lelliott, & Seale, 2004;Meehan et al, 2006;Stubner et al, 2006;Cardell, 2009;Fluttert, van Meijel, van Leeuwen, Bjørkly, Nijman, & Grypdonck 2011;Manna, 2010). Such concerns have led to 'the re-articulation of mental health work in the language of risk' (Quirk et al, 2004(Quirk et al, , p. 2574 and the emergence of a new emphasis on confinement within secure buildings, which is of special interest in this paper.…”
Section: Contextualising Our Research In the Interdisciplinary Literamentioning
confidence: 99%
“…This in turn makes it more difficult to compare study results and draw conclusions about the usefulness of including protective factors in risk assessment schemes. Despite these limitations, clinicians have reported that protective factors were as important to clinical practice as risk factors (Stübner et al, 2006).…”
Section: Protective Factors In Risk Assessmentmentioning
confidence: 99%
“…43 One survey of clinicians found that "stable dynamic factors" such as current symptoms of mental illness were most important in deciding whether to progress a patient's leave. 44 An earlier study found similar factors to be important in understanding how clinicians perceive a forensic patient's risk of violence. 45 A prospective review of 60 unauthorised absences which occurred during more than 70,000 leave episodes from a medium secure unit in the west of England found that unauthorised absences occur for many different reasons including poor clinical decision-making, a deterioration in the patient's mental state or external factors.…”
Section: Prediction Of Abscondingmentioning
confidence: 93%